Tertiary Education Management in Nigeria - ADA’U ADAMU AHMAD; SAADATU TIJJANI AHMAD; Victor Olugbenga AYOKO (Researchparks Publishing, 2023)
This paper examined the problems faced by tertiary education management in Nigeria. The paper concluded that concluded that funding challenge, Integrated Payroll and Personnel Information System (IPPIS), indigenization of principal officer problem, brain-drain, inadequate infrastructure facilities, insecurity, lack of current data, weak manager, shortage of staff and strike actions are challenges faced by tertiary education management in Nigeria. Based on these challenges pointed out, the paper recommended the following; increment in budgetary allocation to tertiary institutions, increment in salaries of academic staff, appointment of competent managers to oversee tertiary institutions, provision of adequate infrastructure facilities, generation of current data, employment of more academic staff, provision of adequate security in all tertiary institutions, tertiary institutions should be isolated from Integrated Payroll and Personnel Information System (IPPIS) programme and autonomy should be granted to tertiary institutions (universities) to prevent problems of indigenization of principal officer problem.